Source-Separated Industrial Wastewater Is a Candidate for Biogas Production through Anaerobic Digestion - Jake A. K. Elliott; Christian Krohn; Andrew S. Ball (Fermentation, 2024)
Anaerobic digestion is a potential treatment for industrial wastewater that provides valuable end-products, including renewable energy (biogas). However, waste streams may be too variable, too dilute at high volumes, or missing key components for stable digestion; all factors that increase costs and operational difficulty, making optimisation crucial. Anaerobic digestion may benefit from process intensification, particularly the novel combination of high-strength source-separated wastewater to minimise volume, together with the use of biosolids biochar as a chemical and microbial stabiliser. This study investigates the stability, yield, and microbial community dynamics of the anaerobic digestion of source-separated industrial wastewater from a food manufacturer and a logistics company, using biosolids biochar as an additive, focusing on gas and volatile fatty acid (VFA) production, process stability, and the microbial community using bench-scale semi-continuous reactors at 30- and 45-day hydraulic retention time (HRT). While gas yields were lower than expected, stability was possible at high HRT. Methane production reached 0.24 and 0.43 L day−1 per litre reactor working volume at 30- and 45-day HRT, respectively, despite high VFA concentration, and was linked to the relative abundance of Methanosarcina in the microbial community. Interactions between substrate, VFA concentration, and the microbial community were observed. Biochar-assisted anaerobic digestion holds promise for the treatment of source-separated wastewater.